(untitled) (Bangladesh Journal of Medical Science, 2015)
Objective: The study was carried out to document the pattern of childhood malignant tumors which were diagnosed at the University of Ilorin Teaching Hospital, Ilorin, and compare with previous reports from other parts of Nigeria and elsewhere and also highlight the challenges and strategies for effective management of these diseases in our environment. Methods: A ten year retrospective analysis of all cancers diagnosed in children below the age of 18 years at the study centre between January 2000 and December 2009 was carried out. Case folders of all children diagnosed with malignant tumors within the study period were retrieved from the Cancer Registry Department of the Hospital and were analyzed with respect to age, gender, morphological or histological type of malignancy, extent of disease, treatment modality, and survival outcome. Results: Ninety nine (99) children were diagnosed with various malignancies during the study period. Sixty seven (67; 67.7%) were boys and 32 (32.3%) were girls giving a male to female ratio of 2:1. There were 22 cases (22.2%) recorded in children aged below 4 years and 72 cases (72.7%) were diagnosed in children between 4-14 years. Lymphomas were the most prevalent malignancies encountered accounting for 54 cases (54.5%), Burkitts lymphoma constituted 43 (79.6%) of all lymphoma cases. The distribution of the five foremost malignancies recorded were as follows: Burkitts lymphoma (43 cases), Nephroblastoma (10 cases), Retinoblastoma (8 cases), Non Hodgkins lymphoma (7 cases) and Acute leukaemias (5 cases). Other malignancies included Osteogenic sarcoma (5), Hodgkins lymphoma (4), and 2 cases each of primary liver cell carcinoma, neuroblastoma, rhabdomyosarcoma and nasopharyngeal tumor. Conclusion: The distribution of the various childhood malignant tumors recorded in this study is similar to the pattern reported in previous studies from Nigeria and other countries. However, there appears to be a lower prevalence of leukemia recorded in this study compared to the earlier findings. The challenges which were identified in the diagnosis, management and overall outcome of our patients included limited number of diagnostic tools, late presentation in the hospital, high patient default rate, poverty, and shortage of chemotherapeutic drugs. Bangladesh Journal of Medical Science Vol.14(3) 2015 p.241-246